System Safety Assessment Based on Past Incidents in Oil and Gas Industries: A Focused Approach in Forecasting of Minor, Severe, Critical, and Catastrophic Incidents, 2010–2015 - Praveen Patel; Nagendra Sohani (Advances in Materials Science and Engineering)
Accident in an occupation which occurred due to series of repetitive minor incidents within the working environment. This work demonstrates the critical system safety assessment based on various incidents that took place to the different system and subsystem of two Indian oil refineries in five years of span 2010 to 2015. The categorization of incidents and hazard rate function of each incident category were classified and calculated. The result of Weibull analysis estimators in the form of scale and shape parameters provides useful information of incidents forecasting and their patterns in a particular time.